Phosphate materials with sodium defects, battery positive electrode materials and sodium ion batteries

A sodium-deficient phosphate material with Co and Fe substitutions addresses the kinetic and stability challenges of sodium-ion batteries, enhancing energy density and electrochemical performance.

CN117228647BActive Publication Date: 2024-12-13TONGJI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210631984.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-07
Publication Date
2024-12-13
Estimated Expiration
2042-06-07

AI Technical Summary

Technical Problem

The transport kinetics of sodium ions is lower than that of lithium ions due to their larger radius, affecting the specific capacity and cycle performance of sodium-ion batteries, and existing cathode materials face issues of stability and electrochemical performance.

Method used

A phosphate material with sodium defects, Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3, is developed through a sol-gel method, incorporating Co and Fe substitutions in the Na3V2(PO4)3 structure to enhance electrochemical activity and stability, generating crystal defects that improve performance.

Benefits of technology

The new material enhances the energy density and electrochemical performance of sodium-ion batteries by increasing Na content, stabilizing redox potential, and improving cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117228647B_ABST
    Figure CN117228647B_ABST
Patent Text Reader

Abstract

This invention provides a phosphate material with sodium defects, a battery cathode material, and a sodium-ion battery, belonging to the field of materials science. The phosphate material with sodium defects has the following characteristics and the chemical formula: Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3, where □ represents an atomic defect. A new NASICON-type phosphate was developed by replacing V in each unit of the Na3V2(PO4)3(NVP) structure with 0.5 Co, 0.5 Fe, and 1 Na. Replacing V with Fe reduced cost, increased Na content, and improved the electrochemical activity of sodium ions in the NASICON-type phosphate structure; replacing V with Co improved the stability range of the redox potential and voltage window, thereby increasing energy density; simultaneously, the substitution process generated crystal defects, enhancing the material's electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a phosphate material with sodium defects, a battery positive electrode material and a sodium ion battery. Background Art

[0002] Energy is the driving force of current social development and the guarantee of human life. Since the 21st century, energy has become a key issue restricting the development of national science and technology. Among various energy storage technologies, advanced electrochemical energy storage such as lithium-ion batteries have received widespread attention. 1-4 . Researchers conducted in-depth research based on traditional lead-acid and nickel-chromium batteries, overcoming the shortcomings of low energy density, low safety and environmental pollution, making lithium-ion batteries widely used in electric vehicles and mobile electronic devices. However, the successful commercialization of lithium-ion batteries has inevitably caused the consumption of a large amount of lithium resources, and lithium resources themselves are relatively limited. Therefore, people have turned their attention to sodium-ion batteries, which have the same working principle and similar composition as lithium-ion batteries. Compared with lithium-ion batteries, sodium-ion batteries have significant advantages such as low price and abundant reserves. 5,6 Sodium is an extremely abundant resource on Earth and is easy to mine. However, since the radius of sodium ions (1.02) is 34% larger than that of lithium ions (0.76), its transport kinetics is much lower than that of lithium, which affects the specific capacity and cycle performance of the battery. Therefore, improving reaction kinetics and developing new electrode materials with better electrochemical performance and better stability are the directions that many researchers are constantly exploring.

[0003] At present, three types of cathode materials have received great attention, namely Prussian blue-like materials, layered oxides and polyanion materials. The purity and water content of Prussian blue materials seriously affect the performance of the material. 7 ; Research on layered cathode materials is mainly focused on the P2 phase and the O3 phase. This type of electrode material has a high theoretical capacity, but poor stability8; NASICON-type polyanion materials have a three-dimensional structural framework. This structure not only has a large space gap, which facilitates the rapid transmission of ions, but also has high chemical stability9. Among polyanion-type cathode materials, Na3V2(PO4)3(NVP) is one of the most widely studied NASICON cathode materials and the most representative. The transition metal elements in the material structure can be replaced, so elements with higher redox potentials such as Co, Cr, etc. can be used to replace V, thereby developing new high-energy-density cathode materials.

[0004] References

[0005] 1.Larcher,D.;Tarascon,J.M.,Towards greener and more sustainablebatteries for electrical energy storage.Nature Chemistry 2015,7(1),19-29.

[0006] 2.Scrosati,B.;Hassoun,J.;Sun,Y.-K.,Lithium-Ion Batteries.A Look intothe Future.Energy Environ.Sci.2011,4(9),3287-3295.

[0007] 3.Tarascon,J.-M.,Is Lithium the New Gold?Nat.Chem.2010,2(6),510-510.

[0008] 4.Li,M.;Lu,J.;Chen,Z.;Amine,K.,30Years of Lithium-IonBatteries.Adv.Mater.2018,30(33),1800561.

[0009] 5.Slater,M.D.;Kim,D.;Lee,E.;Johnson,C.S.,Sodium-IonBatteries.Adv.Funct.Mater.2013,23(8),947-958.

[0010] 6.Vaalma,C.;Buchholz,D.;Weil,M.;Passerini,S.,A Cost and ResourceAnalysis of Sodium-Ion Batteries.Nat.Rev.Mater.2018,3(4),18013.

[0011] 7.You,Y.;Wu,X.-L.;Yin,Y.-X.;Guo,Y.-G.,High-quality Prussian bluecrystals as superior cathode materials for room-temperature sodium-ionbatteries.Energy&Environmental Science 2014,7(5),1643-1647.

[0012] 8.Xu,G.-L.;Amine,R.;Xu,Y.-F.;Liu,J.;Gim,J.;Ma,T.;Ren,Y.;Sun,C.-J.;Liu,Y.;Zhang,X.;Heald,S.M.;Solhy,A.;Saadoune,I.;Mattis,W.L.;Sun,S.-G.;Chen,Z.;Amine,K.,Insights into the structural effects of layered cathode materialsfor high voltage sodium-ion batteries.Energy&Environmental Science 2017,10(7),1677-1693.

[0013] 9.Chen,S.;Wu,C.;Shen,L.;Zhu,C.;Huang,Y.;Xi,K.;Maier,J.;Yu,Y.,Challenges and Perspectives for NASICON-Type Electrode Materials for AdvancedSodium-Ion Batteries.Adv.Mater.2017,29(48),1700431.

[0014] 10.Grosvenor,A.P.;Kobe,B.A.;Biesinger,M.C.;McIntyre,N.S.,Investigation of multiplet splitting of Fe 2p XPS spectra and bonding in ironcompounds.Surf.Interface Anal.2004,36(12),1564-1574.

[0015] 11.Hadouchi,M.;Yaqoob,N.;Kaghazchi,P.;Tang,M.;Liu,J.;Sang,P.;Fu,Y.;Huang,Y.;Ma,J.,Fast Sodium Intercalation in Na 3.41 £ 0.59FeV(PO4)3:A NovelSodium-Deficient NASICON Cathode for Sodium-Ion Batteries.Energy StorageMater.2021,35,192-202. Summary of the invention

[0016] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a phosphate material with sodium defects, a battery positive electrode material and a sodium ion battery.

[0017] The present invention provides a phosphate material with sodium defects, which has the following characteristics and chemical formula: Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3, □ represents atomic defect.

[0018] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the synthesis method of the phosphate material with sodium defects is any one of a solid phase reaction method, a sol-gel method, a sintering method and a solvent thermal method.

[0019] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the synthesis method of the phosphate material with sodium defects is a sol-gel method, which specifically includes the following steps: step 1, dissolving NH4VO3 in a solution containing citric acid as a reducing agent to obtain solution A; step 2, dissolving Fe(NO3)3.9H2O, (CH3COO)2Co.4H2O and CH3COONa in ultrapure water to obtain solution B; step 3, mixing solution A and solution B and stirring for a first predetermined time, adding NH4H2PO4 and heating the mixed solution to a first predetermined temperature until it becomes a gel to obtain a precursor; step 4, heat-treating the precursor to obtain the phosphate material with sodium defects.

[0020] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the molar ratio of CH3COONa, NH4VO3, (CH3COO)2Co.4H2O, Fe(NO3)3.9H2O and NH4H2PO4 is 3.6:0.5:0.5:1:3.

[0021] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the first predetermined time is 25 minutes to 30 minutes, and the first predetermined temperature is 80°C.

[0022] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the heat treatment process includes: heat treating a precursor at a second predetermined temperature for a second predetermined time to obtain a solid powder, and heating the powder at a third predetermined temperature for a third predetermined time under argon to obtain a phosphate material with sodium defects, wherein the second predetermined temperature is 180°C to 210°C, the second predetermined time is 3.5h to 4h, the third predetermined temperature is 630°C to 650°C, and the third predetermined time is 12h to 13h.

[0023] The phosphate material with sodium defects provided by the present invention may also have the following characteristics: wherein the second predetermined temperature is 200° C., the second predetermined time is 4 hours, the third predetermined temperature is 650° C., and the third predetermined time is 12 hours.

[0024] The present invention provides a battery positive electrode material having the following characteristics, comprising: a phosphate material with sodium defects, at least one conductive material and at least one polymer binder, wherein in the battery positive electrode material, the content of the phosphate material with sodium defects is more than 50.0wt%, the content of the conductive material is 10.0wt% to 30.0wt%, and the phosphate material with sodium defects is the above-mentioned phosphate material with sodium defects.

[0025] The battery positive electrode material provided by the present invention may also have the following characteristics: wherein the preparation process of the battery positive electrode material is as follows: a phosphate material with sodium defects, at least one conductive material, at least one polymer binder and a solvent are mixed together, and then coated on a current collector, and the battery positive electrode material is obtained after removing the solvent, the conductive material is conductive carbon, and the conductive carbon is any one of carbon black, Ketjen black and acetylene black, the polymer binder is any one of polyvinylidene fluoride, polytetrafluoroethylene and sodium carboxymethyl cellulose, and the solvent is N-methylpyrrolidone or H2O.

[0026] The present invention provides a sodium ion battery having the following characteristics, comprising: a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode is made of the above-mentioned battery positive electrode material.

[0027] Functions and Effects of the Invention

[0028] According to the phosphate material with sodium defects, the battery positive electrode material and the sodium ion battery involved in the present invention, a new NASICON-type phosphate is developed by replacing V with 0.5 Co, 0.5 Fe and 1 Na in each unit of the Na3V2(PO4)3(NVP) structure, thereby preparing a new Na3V2(PO4)3(NVP)-containing phosphate material with sodium defects. 3.6 □ 0.4 Co 0.5 Fe 0.5V(PO4)3 phosphate material (denoted as NCFVP). Substituting Fe for V reduces the cost, increases the Na content, and improves the electrochemical activity of sodium ions in the NASICON-type phosphate structure; substituting Co for V increases the stability range of the redox potential and voltage window, thereby improving the energy density; at the same time, crystal defects are generated during the substitution process, which improves the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The experimental and simulated XRD patterns of NCFVP powder in Example 1 of the present invention;

[0030] Figure 2 is a schematic diagram of the NCFVP crystal structure in Example 1 of the present invention;

[0031] Figure 3 is the XPS simulation fitting spectrum of Co in the NCFVP in the 2p orbital in Example 1 of the present invention;

[0032] Figure 4 is the XPS simulation fitting spectrum of the Fe 2p orbital in NCFVP in Example 1 of the present invention;

[0033] Figure 5 is the XPS fitting spectrum of O1s and V2p in NCFVP in Example 1 of the present invention;

[0034] Figure 6 is the XPS fitting spectrum of P2p in NCFVP in Example 1 of the present invention;

[0035] Figure 7 The first three CV curves of the sodium ion battery in Example 2 of the present invention at a scan rate of 0.1 mV / s;

[0036] Figure 8 is a constant current charge and discharge curve of the sodium ion battery in Example 2 of the present invention when the voltage window is 2.0-4.0V;

[0037] Fig. 9 This is a cycle performance diagram of the sodium ion battery in Example 2 of the present invention. DETAILED DESCRIPTION

[0038] The present application provides a phosphate material with sodium defects, a battery positive electrode material and a sodium ion battery.

[0039] In this application, the chemical formula of the sodium-deficient phosphate material (NCFVP) is as follows:

[0040] Na 3.6 □ 0.4 Co 0.5Fe 0.5 V(PO4)3, □ represents atomic defect.

[0041] The synthesis of NCFVP can be carried out by any of the solid phase reaction method, sol-gel method, sintering method and solvothermal method.

[0042] The synthesis of NCFVP by sol-gel method includes the following steps:

[0043] Step 1, dissolving NH4VO3 in a solution containing citric acid as a reducing agent to obtain solution A;

[0044] Step 2, dissolving Fe(NO3)3.9H2O, (CH3COO)2Co.4H2O and CH3COONa in ultrapure water to obtain solution B;

[0045] Step 3, after mixing solution A and solution B and stirring for 25 to 30 minutes, NH4H2PO4 is added and the mixed solution is heated to 80° C. until it becomes a gel to obtain a precursor;

[0046] Step 4, heat-treating the precursor at 180° C. to 210° C. for 3.5 h to 4 h to obtain a solid powder, and heating the powder at 630° C. to 650° C. under argon for 12 h to 13 h to obtain NCFVP.

[0047] Among them, the molar ratio of CH3COONa, NH4VO3, (CH3COO)2Co.4H2O, Fe(NO3)3.9H2O and NH4H2PO4 is 3.6:0.5:0.5:1:3.

[0048] In the present application, the positive electrode material of the battery is composited by NCFVP, at least one conductive material and at least one polymer binder. The content of NCFVP is more than 50.0wt%, and the content of the conductive material is 10.0wt% to 30.0wt%. The conductive material is generally conductive carbon, such as carbon black, Ketjen black and acetylene black; the polymer binder can be polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), or sodium carboxymethyl cellulose (CMC).

[0049] The positive electrode material can be prepared by the following steps:

[0050] A slurry containing NCFVP, conductive material, polymer binder and a suitable solvent is coated on a current collector (such as aluminum foil) and then placed in an oven at 80°C for 12 hours to remove the solvent. The slurry is prepared by mixing NFVP, conductive material, polymer binder and solvent, and the solvent is N-methylpyrrolidone (NMP) or H2O.

[0051] In the present application, the sodium ion battery comprises a negative electrode, a positive electrode, an electrolyte and a separator. The negative electrode is made of sodium metal or a carbon-based material (such as hard carbon). The positive electrode is made of the above positive electrode material.

[0052] The electrolyte can be a solid composed of an inorganic sodium conductor or a sodium conductive polymer, or it can be a liquid and composed of a sodium salt, which is dissolved in a mixture of solvents, and different types of solvents or additives can be selected. Sodium salts are preferably selected from NaPF6, NaClO4, etc. Sodium salts are better dissolved in organic solvents based on carbonates, and organic carbonate solvents containing unsaturated cyclic carbonate groups (such as ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate and fluoropropylene carbonate) and unsaturated acyclic carbonates (such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and fluorinated acyclic carbonates, etc.) can be selected. Some ester solvents are also suitable for use in combination with carbonates (such as propyl propionate, ethyl propionate, etc.). When the electrolyte is a liquid, a diaphragm is required in the battery. The material of the diaphragm is usually glass fiber (such as GF / D or GF / A, Whatman Company).

[0053] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments are combined with the accompanying drawings to specifically describe the phosphate material with sodium defects, the battery positive electrode material and the sodium ion battery of the present invention.

[0054] <Example 1>

[0055] Example 1 provides a sodium-deficient phosphate material (NCFVP), a preparation method thereof, and characterization thereof.

[0056] The chemical formula of NCFVP is as follows:

[0057] Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3, □ represents atomic defect.

[0058] NCFVP is synthesized by sol-gel method, which specifically includes the following steps:

[0059] Step 1, dissolving 2 mmol NH4VO3 in 20 mL ultrapure water at 80°C containing citric acid (1.5 g) as a reducing agent to obtain solution A;

[0060] Step 2, dissolving Fe(NO3)3.9H2O, (CH3COO)2Co.4H2O and CH3COONa in 40 mL of ultrapure water to obtain solution B;

[0061] Step 3, after mixing solution A and solution B and stirring for 25 to 30 minutes, 6 mmol NH4H2PO4 is added and the mixed solution is heated to 80° C. until it becomes a gel to obtain a precursor;

[0062] Step 4, heat-treating the precursor at 200° C. for 4 h to obtain a solid powder, and heating the powder at 650° C. for 12 h under argon to obtain NCFVP powder.

[0063] Among them, the molar ratio of CH3COONa, NH4VO3, (CH3COO)2Co.4H2O, Fe(NO3)3.9H2O and NH4H2PO4 is 3.6:0.5:0.5:1:3.

[0064] In order to prove that the pure phase target compound was obtained, X-ray powder diffraction was performed at room temperature using a D8Advance X-ray diffractometer from Bruker, Germany, with a scanning mode of θ–θ and a radiation source of Cu Kα ( ). Data were collected in the 2θ range of 10°≤2θ≤100° with a step size of 0.0148°. The structure of NCFVP was refined by the Rietveld method. The new phosphate crystal structure obtained after refinement belongs to the trigonal system with a space group of

[0065] Table 1. Crystal data, data collection and structure refinement results of NCFVP

[0066]

[0067]

[0068] As shown in Table 1, the refinement results show that in the crystallographic model, Co1, Fe1 and V1 share the crystallographic position 12c, with occupancy rates of 25%, 25% and 50% respectively. Sodium atoms Na1 and Na2 are located at special positions 6b and 18e, with occupancy rates of 1 and 0.86 respectively, that is, there is 1 sodium atom at the Na1 position and 2.6 sodium atoms at the Na2 position per unit cell; so the final chemical formula of the material is determined to be Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3.

[0069] Figure 1 These are the experimental and simulated XRD patterns of the NCFVP powder in Example 1 of the present invention.

[0070] like Figure 1 As shown, the experimental map of the refined crystal structure is in good agreement with the calculated map.

[0071] Figure 2 It is a schematic diagram of the NCFVP crystal structure in Example 1 of the present invention.

[0072] like Figure 2 As shown in Table 1, NCFVP crystals belong to the NASICON type structure, which is composed of shared corner positions of PO4 tetrahedrons and (Co / Fe / V)O6 octahedrons and extends in three-dimensional space to form a three-dimensional open stable framework. Na1 atoms form six coordinations with oxygen atoms, and Na2 atoms are eight coordinations and are located at the same z position as phosphorus atoms. The crystallographic data and structural refinement details are shown in Table 1.

[0073] X-ray photoelectron spectroscopy (XPS) was performed on an ESCALAB 250Xi photoelectron spectrometer using an Al Kα source. In order to determine the oxidation state of cobalt and iron in NCFVP, standard samples were used for simulation fitting and comparison based on the complex multiplet splitting spectral characteristics of most transition metals.

[0074] Figure 3 This is the XPS simulation fitting spectrum of Co in the NCFVP in Example 1 of the present invention in the 2p orbital.

[0075] The Co 2p spectrum is the same as that of the comparative CoO compound; the measured Co 2p 3 / 2 Spectrum Figure 3 As shown, for qualitative chemical analysis, good fitting results were obtained based on the standard spectrum of the benchmark sample and references, proving that the Co incorporated in the structure is all +2 valence.

[0076] Figure 4 It is a simulation fitting diagram of the XPS nuclear energy level spectrum of the Fe 2p orbital in the NCFVP in the first embodiment of the present invention.

[0077] The Fe 2p energy level fitting of Fe is simulated after uniform normalization according to the standard samples FeO and Fe2O3, such as Figure 4 As shown in the simulation results, Fe 2+ and Fe 3+ The fitting results (fitting curves) obtained after the peak overlap match the actual experimental values ​​well; in the simulation process, Fe with a ratio of 0.21 and 0.79 were used respectively. 2+ and Fe 3+ To fit, we get Fe 2+ / Fe 3+ The corresponding proportion.

[0078] According to the fitting results of Fe, it can be calculated that the ratio of +2 and +3 valence in doped iron is 0.21:0.79, proving that there are 0.4 cation defects in each unit structure, which is consistent with the refinement results.

[0079] Figure 5 It is the XPS fitting spectrum of O1s and V2p in NCFVP in Example 1 of the present invention.

[0080] like Figure 5 As shown in the fitted V 2p and O1s spectra, it can be clearly seen that the broad peaks at 523.14 eV and 516.38 eV correspond to the V 2p 1 / 2 and V 2p 3 / 2 Core energy level, belongs to V 3+ The V 2p peak becomes broader and has a lower binding energy, which is consistent with the vanadium (III)-based compounds reported in the literature.

[0081] Figure 6 It is the XPS fitting spectrum of P2p in NCFVP in Example 1 of the present invention.

[0082] like Figure 6 As shown in Figure 2, the XPS spectrum of P 2p is fitted, and the peaks at 132.94 eV and 132.06 eV can be corresponding to P 2p, respectively. 1 / 2 and P 2p 3 / 2 The core energy level of PO4 generates a splitting energy of 0.88 eV between the energy levels. 3- existence.

[0083] <Example 2>

[0084] Example 2 provides a battery positive electrode material and a sodium ion battery prepared using the NCFVP prepared in Example 1.

[0085] The positive electrode material of the battery is composed of 70wt.% NCFVP, 20wt.% conductive carbon black (Super P), and 10wt.% polyvinylidene fluoride (PVDF, binder).

[0086] The positive electrode material is prepared by the following steps:

[0087] A slurry containing 70 wt.% NCFVP, 20 wt.% conductive carbon black (Super P), 10 wt.% polyvinylidene fluoride and a suitable solvent (NMP) is coated on a current collector (such as aluminum foil), and then dried at 80°C for 12 hours to remove the solvent. The slurry is prepared by mixing NFVP, a conductive material, a polymer binder and a solvent.

[0088] The sodium ion battery includes a negative electrode, a positive electrode, an electrolyte and a diaphragm. Among them, the positive electrode is made of the above-mentioned battery positive electrode material, and its pole piece is a disc with a diameter of 8 mm; the negative electrode is made of sodium metal; glass fiber (GF / D, Whatman) is used as a diaphragm; the electrolyte is a conventional sodium ion battery electrolyte purchased directly. The button battery (CR2025) was assembled in a glove box filled with argon. The constant current cycle charge and discharge test was carried out using the NEWARE battery test system. The cyclic voltammetry test was carried out using the Bio-Logic VMP-3 electrochemical workstation.

[0089] Figure 7 It is the first three CV curves of the sodium ion battery in Example 2 of the present invention at a scan rate of 0.1 mV / s.

[0090] like Figure 7 As shown in the cyclic voltammetry curve tested in the voltage range of 2.0-4.0 V at a scan rate of 0.1 mV / s, there are two oxidation peaks at ~2.50 V and ~3.49 V, corresponding to Fe 2+ / Fe 3+ and V 3+ / V 4+ .

[0091] Figure 8 It is the constant current charge and discharge curve of the sodium ion battery in Example 2 of the present invention when the voltage window is 2.0-4.0V.

[0092] like Figure 8 As shown, in the voltage range of 2.0-4.0V, NCFVP is heated at 0.1C (1C is equivalent to exchanging 2 Na + ), two reversible charge-discharge voltage platforms at ~2.50 V and ~3.49 V can be clearly observed, which correspond to Fe 2+ / Fe 3+ and V 3+ / V 4+ , which is in good agreement with the CV curve. The charge and discharge capacities after activation are 158 and 155 mA g -1 The material has an initial Coulombic efficiency of 98%, indicating low sodium loss during the initial charge and discharge process, which makes this new NASICON phosphate promising for use as the cathode for SIB full cells.

[0093] Fig. 9 It is a cycle performance diagram of the sodium ion battery NCFVP in the second embodiment of the present invention.

[0094] like Fig. 9 As shown in Figure 2, NCFVP has very stable long-term cycling performance at a current rate of 5C. The electrode can deliver 124.2 mAh g at 2C.-1 Even when the current is increased to 5C, 82.96 mAh g -1 Even after 500 cycles, the sodium-ion battery can still maintain 63.86 mAh g -1 The capacity of NCFVP decays by 0.04% per cycle on average, which indicates that NCFVP has good capacity retention in long-term cycling.

[0095] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A phosphate material having sodium defects, characterized in that: The chemical formula is as follows: Na 3.6 □ 0.4 Co 0.5 Fe 0.5 V(PO4)3, □ represents atomic defects, Wherein, the synthesis method of the phosphate material with sodium defects is a sol-gel method.

2. The sodium-deficient phosphate material according to claim 1, Features: in, The synthesis method of the sodium-deficient phosphate material specifically comprises the following steps: Step 1, dissolving NH4VO3 in a solution containing citric acid as a reducing agent to obtain solution A; Step 2, dissolving Fe(NO3)3.9H2O, (CH3COO)2Co.4H2O and CH3COONa in ultrapure water to obtain solution B; Step 3, after mixing the solution A and the solution B and stirring for a first predetermined time, adding NH4H2PO4 and heating the mixed solution to a first predetermined temperature until it becomes a gel, thereby obtaining a precursor; Step 4: heat-treating the precursor to obtain the phosphate material with sodium defects.

3. The sodium-deficient phosphate material according to claim 2, characterized in that: in, The molar ratio of the CH3COONa, the NH4VO3, the (CH3COO)2Co.4H2O, the Fe(NO3)3.9H2O and the NH4H2PO4 is 3.6:0.5:0.5:1:

3.

4. The sodium-deficient phosphate material according to claim 2, characterized in that: in, The first predetermined time is 25 minutes to 30 minutes, The first predetermined temperature is 80°C.

5. The sodium-deficient phosphate material according to claim 2, characterized in that: in, The heat treatment process includes: heat-treating the precursor at a second predetermined temperature for a second predetermined time to obtain a solid powder, and heating the powder at a third predetermined temperature for a third predetermined time under argon to obtain the sodium-deficient phosphate material, The second predetermined temperature is 180° C. to 210° C., the second predetermined time is 3.5 h to 4 h, The third predetermined temperature is 630° C. to 650° C., and the third predetermined time is 12 hours to 13 hours.

6. The sodium-deficient phosphate material according to claim 5, characterized in that: in, The second predetermined temperature is 200° C., the second predetermined time is 4 hours, The third predetermined temperature is 650° C., and the third predetermined time is 12 hours.

7. A battery positive electrode material, characterized in that: include: a phosphate material having sodium defects, at least one conductive material and at least one polymer binder, Wherein, in the battery positive electrode material, the content of the phosphate material with sodium defects is more than 50.0wt%, and the content of the conductive material is 10.0wt% to 30.0wt%, The phosphate material having sodium defects is the phosphate material having sodium defects as claimed in any one of claims 1 to 6.

8. The battery positive electrode material according to claim 7, characterized in that: in, The preparation process of the battery positive electrode material is as follows: The phosphate material having sodium defects, the at least one conductive material, the at least one polymer binder and a solvent are mixed together, and then coated on a current collector, and the battery positive electrode material is obtained after removing the solvent, The conductive material is conductive carbon, which is any one of carbon black, Ketjen black and acetylene black. The polymer binder is any one of polyvinylidene fluoride, polytetrafluoroethylene and sodium carboxymethyl cellulose, The solvent is N-methylpyrrolidone or H2O.

9. A sodium ion battery, characterized in that: include: Negative electrode, positive electrode and electrolyte, Wherein, the positive electrode is made of the battery positive electrode material according to claim 7 or 8.

Citation Information

Patent Citations

  • Material with mixture of ions with sodium vanadium phosphate cathode material coated by carbon and preparing method thereof

    CN106328911A

  • Positive electrode material for transition metal-doped sodium ion battery and preparation and application thereof

    CN109755565A

  • High-performance sodium defect type positive electrode material and sodium ion battery

    CN110993942A